What happened to gay life? - Reynolds, Robert, 1965- (University of New South Wales Press, 2007)
In 2002 the Sydney Gay and Lesbian Mardi Gras went bankrupt. It struggles on, but Gay Sydney isn't what it used to be--a shining international beacon of hedonistic homosexuality that was an economic and a political force. This very engaging book tries to find out what happened to gay life. Robert Reynolds talks to numerous gay men--some whose lives are committed to struggling for gay rights, others whose major struggle has been for the right to party and some for whom being gay is no big deal. The book raises lots of questions about what being gay means as gay life becomes mainstream.